2020
DOI: 10.1017/wet.2020.56
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Arkansas Palmer amaranth accessions to common herbicide sites of action

Abstract: Palmer amaranth is one of the most difficult-to-control weeds in row crop systems and has evolved resistance to several herbicide sites of action (SOAs). A late-season weed-escape survey had been conducted earlier to determine the distribution of protoporphyrinogen oxidase–inhibitor resistant Palmer Amaranth in Arkansas. The objective of this study was to evaluate the susceptibility of Arkansas Palmer amaranth accessions to commonly used herbicide SOAs. The SOAs evaluated were group 2 + 9, 3, 4, 5, 10, 14, 15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Due to both economic and environmental factors, post-emergence application of ALS-inhibiting herbicides is the most common weed control strategy in soybean in Italy, and it is likely one of the driving factors of the recent spreading of ALS-resistant amaranths [15]. Several herbicides with alternative sites of action, such as inhibitors of photosystem (PS) I and II, 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase and carotenoid biosynthesis can provide effective control of ALS-resistant populations of A. palmeri [16,17]. However, given the ability of this species to evolve resistance against herbicides with different sites of action [18], the efficacy of potential alternative herbicides should be assessed at local level before recommending their use.…”
Section: Introductionmentioning
confidence: 99%
“…Due to both economic and environmental factors, post-emergence application of ALS-inhibiting herbicides is the most common weed control strategy in soybean in Italy, and it is likely one of the driving factors of the recent spreading of ALS-resistant amaranths [15]. Several herbicides with alternative sites of action, such as inhibitors of photosystem (PS) I and II, 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase and carotenoid biosynthesis can provide effective control of ALS-resistant populations of A. palmeri [16,17]. However, given the ability of this species to evolve resistance against herbicides with different sites of action [18], the efficacy of potential alternative herbicides should be assessed at local level before recommending their use.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that compared to other herbicide SOA, there is a more rapid evolution of sub-lethal dose-mediated mesotrione resistance in A. palmeri . The rapid selection for resistance to HPPD herbicides is not surprising considering the failure of a labeled rate of mesotrione (105 g ai ha −1 ) and tembotrione (92 g ai ha −1 ) to control A. palmeri accessions throughout Arkansas in recent screenings [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under greenhouse conditions, the use of sub-lethal mesotrione rates over several generations selected for resistance in this population was demonstrated. Recent screenings for sensitivity of A. palmeri accessions in Arkansas to mesotrione and tembotrione revealed that a highly variable response was present among sampled sites [ 31 , 32 ]. The evolution of mesotrione resistance under field conditions is possible if reduced herbicide rates are applied for economic reasons, weeds emerge as soil-applied activity of the herbicide partially dissipates, the herbicide is applied to larger weeds than recommended, or environmental conditions are such that they lead to reduced herbicide efficacy [ 35 , 36 , 37 ] because all these scenarios may allow for the selection and accumulation of minor effect resistance conferring alleles in the population.…”
Section: Discussionmentioning
confidence: 99%
“…The resistant and susceptible accessions used in this study were documented in earlier experiments described elsewhere [10,27]. In order to characterize the resistance to trifluralin, the resistant accession was further evaluated.…”
Section: Plant Materialsmentioning
confidence: 99%